Yao Souchou. Confucian Capitalism. Discourse, Practice and the Myth of the Chinese Enterprise. Londres: Routledge Curzon. Taylor & Francis Group, 2002 - Cornejo, Romer (Estudios de Asia y África, 2004)
-